Neoliberal economic reforms, the rich and the poor in Bangladesh - Nuruzzaman, Mohammed (2004)
Bangladesh has been implementing neoliberal structural adjustment policies since the early 1980s. This article analyzes the economic and social outcomes the reform policies have created in the past two decades. It argues that the reform policies, instead of distributing benefits among different societal groups, have brought an economic windfall mainly for the business and industrial class in Bangladesh. Compared to the 24 families of erstwhile United Pakistan, there is now a small group of 40 to 50 families who effectively control the total industrial and financial assets of this poor nation. The vast majority of other societal groups and classes - the industrial and agricultural labor, small businesses, marginal and small farmers, and urban and rural poor - are left out by the reform agenda. The lack of policies of distributional justice has resulted in widening disparities in income and wealth between the low and high strata of the society and deterioration is the overall poverty situation of the country. - Reproduced.
Keywords: Economic reform - Bangladesh; Economic reform